Ethical Considerations of Generation Ships: A Bioethical Analysis - Sinan, Israa; Park, Gavin (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Generation ships are a concept in science fiction that represents a spaceship designed for long space journeys which travel over multiple generations to a final destination. Throughout the paper, this science fiction concept is a metaphor for human life on earth, to examine the transgenerational effects on definitions of person, privacy, and death, and analyzing how major bioethical principles apply.